Controlled local drug delivery strategies from chitosan hydrogels for wound healing. (3rd July 2017) - Elviri, Lisa; Bianchera, Annalisa; Bergonzi, Carlo; Bettini, Ruggero
ABSTRACT: Introduction: The main target of tissue engineering is the preparation and application of adequate materials for the design and production of scaffolds, that possess properties promoting cell adhesion, proliferation and differentiation. The use of natural polysaccharides, such as chitosan, to prepare hydrogels for wound healing and controlled drug delivery is a research topic of wide and increasing interest. Areas covered: This review presents the latest results and challenges in the preparation of chitosan and chitosan-based scaffold/hydrogel for wound healing applications. A detailed overview of their behavior in terms of controlled drug delivery, divided by drug categories, and efficacy was provided and critically discussed. Expert opinion: The need to establish and exploit the advantages of natural biomaterials in combination with active compounds is playing a pivotal role in the regenerative medicine fields. The challenges posed by the many variables affecting tissue repair and regeneration need to be standardized and adhere to recognized guidelines to improve the quality of evidence in the wound healing process. Currently, different methodologies are followed to prepare innovative scaffold formulations and structures. Innovative technologies such as 3D printing or bio-electrospray are promising to create chitosan-based scaffolds with finely controlled structures with customizable shape porosity and thickness. Chitosan scaffolds could be designed in combination with a variety of polysaccharides or active compounds with selected and reproducible spacial distribution, providing active wound dressing with highly tunable controlled drug delivery.